PsycEXTRA Dataset 2011
DOI: 10.1037/e741452011-009
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of links between components of empathy and interpersonal problems

Abstract: Four components of empathy were assessed to determine their contribution to six common interpersonal problems. A sample of 251 undergraduate students (129 women, 122 men) were administered the Inventory of Interpersonal Problems (IIP) and the Interpersonal Reactivity Index (IRI) in order to evaluate the link between these measures. Regression analyses were used to evaluate which component of empathy was the greatest contributor to the interpersonal problems. Personal distress was found to contribute to difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The negative association between hoarding and self-reported or behavioural cognitive empathy when taken together with emotional empathy results may partially explain the interpersonal difficulties experienced in individuals who hoard. For example, a study by Lange and Couch (2011) found that the personal distress subscale of the Interpersonal Reactivity Index (used as a measure of emotional empathy) is positively associated with interpersonal difficulties such as difficulties being assertive, sociable, submissive, responsible, and controlling, whereas the perspective-taking subscale (used as a measure of cognitive empathy) was associated with submissiveness, difficulties with control, sociability, and intimacy. This apparent imbalance with excess emotional empathy on the one hand, and impaired cognitive empathy on the other, fits with suggestions that balanced levels of both cognitive and emotional empathy facilitate prosocial behaviour and successful social functioning (Smith, 2009).…”
Section: Hoarding and Cognitive Empathymentioning
confidence: 99%
“…The negative association between hoarding and self-reported or behavioural cognitive empathy when taken together with emotional empathy results may partially explain the interpersonal difficulties experienced in individuals who hoard. For example, a study by Lange and Couch (2011) found that the personal distress subscale of the Interpersonal Reactivity Index (used as a measure of emotional empathy) is positively associated with interpersonal difficulties such as difficulties being assertive, sociable, submissive, responsible, and controlling, whereas the perspective-taking subscale (used as a measure of cognitive empathy) was associated with submissiveness, difficulties with control, sociability, and intimacy. This apparent imbalance with excess emotional empathy on the one hand, and impaired cognitive empathy on the other, fits with suggestions that balanced levels of both cognitive and emotional empathy facilitate prosocial behaviour and successful social functioning (Smith, 2009).…”
Section: Hoarding and Cognitive Empathymentioning
confidence: 99%
“…Failure to adjust to the social world may lead students to increase the likelihood of suffering from various psycho-social problems (Lange & Couch, 2011;Saleem et al, 2014). Most typical difficulties encountered by university students are mood disruptions, problematic behavior, interpersonal problems, and deterioration of self-esteem (Chung et al, 2017;Matin & Khan, 2017) which are associated with numerous adverse outcomes including low self-esteem, loneliness, substance use and poor academic performance (De Clercq et al, 2022;New & Ghafar, 2016).…”
mentioning
confidence: 99%